2022
DOI: 10.2106/jbjs.22.00746
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fibular Allograft Augmentation in Medial Column Comminuted Proximal Humeral Fractures

Abstract: Background:Previous observational studies and meta-analyses have recommended augmentation with a fibular allograft (FA) during the treatment of proximal humeral fractures with locking plates (LPs). However, to our knowledge, randomized controlled trials comparing open reduction and internal fixation (ORIF) with and without FA have not been performed to date.Methods:This was a randomized controlled trial in which adults with a medial column comminuted proximal humeral fracture were randomly allocated to undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…From a biomechanical perspective, the intramedullary calcar support plate, allograft, and lateral locking plate were used together to stabilize and support the proximal humeral fractures effectively. Some studies have used large autogenous/allogeneic fibular grafts to treat complex proximal humeral fractures [ 32 , 42 , 43 ], reducing postoperative reduction loss and increasing the fracture union rate compared to the control group. Our results are consistent with these studies.…”
Section: Discussionmentioning
confidence: 99%
“…From a biomechanical perspective, the intramedullary calcar support plate, allograft, and lateral locking plate were used together to stabilize and support the proximal humeral fractures effectively. Some studies have used large autogenous/allogeneic fibular grafts to treat complex proximal humeral fractures [ 32 , 42 , 43 ], reducing postoperative reduction loss and increasing the fracture union rate compared to the control group. Our results are consistent with these studies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent randomized controlled study showed that using a fibula allograft did not result in better outcomes or less complications. 34 However, this study only included patients with medial comminuted fractures in elderly patients and also included fracture type Neer 2. Moreover, the study compared heterogeneous groups (fibular allograft vs. locking plates) whereas our study matched cases one on one.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the study compared heterogeneous groups (fibular allograft vs. locking plates) whereas our study matched cases one on one. 34 We specifically included patients with anatomical neck fractures which are more likely to collapse. This might exactly be the reason why we found better outcomes in the fibula group.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of restoration of the medial column has been suggested to contribute to fixation failure. An RCT compared clinical and radiographic outcomes following locking plate fixation with (39 patients) or without (41 patients) a fibular allograft for proximal humeral fractures with medial column comminution 2 . There was no clinically important improvement in the Disabilities of the Arm, Shoulder and Hand (DASH) score or improvement in postoperative radiographs with addition of fibular allograft augmentation at 1 year.…”
Section: Shouldermentioning
confidence: 99%